Ethics in Surgical Innovations from the Patient Perspective - Eyers, Tony; Krastev, Yordanka (Yearbook of Medical Informatics, 2020)
Objective: Surgical innovation (SI) can place patients at risk. We sought to explore what clinical information is readily available to patients who have been offered innovative surgical procedures, using two examples drawn from our recent experience: one a surgical technique, and the other a prosthetic material. We wanted to determine from our review the extent to which information available on the Internet might augment the medical literature and help satisfy the ethical requirements for patients to be adequately informed before they proceed with innovative surgery.Methods: A scoping review of the medical literature was performed to look for studies addressing the review aims; targeted searches on Google, YouTube, and patient websites were carried out to find readily available patient information on two chosen innovative surgical procedures. We conducted a content analysis of the selected references to determine the availability, relevance, and the utility of the published information to a layperson.Results: Medical database searches identified 614 records, 91 were screened and only six were relevant. The Internet searches returned thousands of results; however, we limited our screening to the first five pages of results for those sources. From both types of searches, 348 references were excluded because they did not meet the inclusion criteria and 51 were included in the analysis. The findings are presented in four themes: safety and feasibility of the technique, availability and accessibility to a layperson, relevance and utility to a layperson, and commercial information.Conclusion: The review has shown that lay people seeking to find out more about the two innovations would get very little useful information from Google, YouTube, or patient websites. Practitioners offering SI should provide sufficient information to allow their patients to make an autonomous decision about whether to proceed. For major SI, we encourage innovators to develop a plain language statement that would be made available on the Internet to the mutual advantage of both innovators and patients.
Keywords: Ethics; surgical innovation; patient information; social media; internet